2020
DOI: 10.3390/ijms21238975
|View full text |Cite
|
Sign up to set email alerts
|

NPM1-Mutated Myeloid Neoplasms with <20% Blasts: A Really Distinct Clinico-Pathologic Entity?

Abstract: Nucleophosmin (NPM1) gene mutations rarely occur in non-acute myeloid neoplasms (MNs) with <20% blasts. Among nearly 10,000 patients investigated so far, molecular analyses documented NPM1 mutations in around 2% of myelodysplastic syndrome (MDS) cases, mainly belonging to MDS with excess of blasts, and 3% of myelodysplastic/myeloproliferative neoplasm (MDS/MPN) cases, prevalently classified as chronic myelomonocytic leukemia. These uncommon malignancies are associated with an aggressive clinical course, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 124 publications
0
22
0
Order By: Relevance
“…NPM1 mutations are recurrent molecular lesions, occurring in nearly 30% of AML patients, are stable across the disease course and are considered to be driver events, highly specific for leukemogenesis [5,[7][8][9][10]. Indeed, NPM1-mutated C-terminal aminoacidic sequences are not found in either malignancies different from AML or normal tissues, resulting in leukemiaspecific neoantigens considered optimal target for immunotherapy [2,3,15,16,19,20,88,89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPM1 mutations are recurrent molecular lesions, occurring in nearly 30% of AML patients, are stable across the disease course and are considered to be driver events, highly specific for leukemogenesis [5,[7][8][9][10]. Indeed, NPM1-mutated C-terminal aminoacidic sequences are not found in either malignancies different from AML or normal tissues, resulting in leukemiaspecific neoantigens considered optimal target for immunotherapy [2,3,15,16,19,20,88,89].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to this, nucleophosmin (NPM1) gene mutations, observed in nearly 30% of adult AML patients, accounting for approximately 50-60% of cases among the cytogenetically normal AML subgroup, represent one of the most frequent genetic lesions documented in AML [5][6][7][8]. Moreover, NPM1 mutations are highly specific, being almost exclusively found in AML, and generally expressed in the entire leukemic population, while not detectable in clonal hematopoiesis [5,[7][8][9][10]. As expected for driver genetic lesions, NPM1 mutations are also stable throughout the course of the disease, with most relapses being due to the recurrence of the original NPM1-mutated clone, whereas only 5% to 10% of recurrent cases are characterized by the absence of NPM1 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…The serial acquirement of somatic mutations in myeloid clone(s) was described as the multistep pathogenesis of AML. Several lines of evidence prove that NPM1 mutations are responsible for the definitive acute leukemic transformation, therefore considered as leukemia founder mutations: (i) NPM1 mutations are completely absent in the population without hematological malignancies even at a higher age [ 22 24 ]; (ii) NPM1 mutations cannot be detected in AML patients months or years before the manifestation of AML [ 25 , 26 ]; (iii) NPM1 mutations occur rather rarely (approximately 2–3%) in preleukemic myeloid malignancies such as myelodysplastic syndrome (MDS) or in myelodysplastic/myeloproliferative neoplasm (MDS/MPN), which are mainly characterized by the progression to overt AML [ 27 ]; (iv) NPM1 mutations were not present in preleukemic hematopoietic stem cells [ 28 , 29 ]. Our observation that NPM1 VAF decreased below 2.5% in all cases with morphologic leukemia-free state, also proved that NPM1 mutations do not occur in the preleukemic state.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also pointed out that the NPM1 mutation was proposed as a secondary event in the conversion of CMML to AML (Courville et al, 2013;Lin and Falini, 2015). Some researchers have suggested that wild-type or mutated NPM1 may be a diagnostic basis for AML, irrespective of bone marrow blast percentage (Forghieri et al, 2020). The study by Xu J et al showed DNMT3A (Arg882) drives CMML through changing gene expression and DNA methylation in hematopoietic cells (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%